Subgenual Cingulate Cortex Functional Connectivity in Relation to Depressive Symptoms and Cognitive Functioning in Type 1 Diabetes Mellitus Patients. Issue 6 (July 2016) - van Duinkerken, Eelco; Ryan, Christopher M.; Schoonheim, Menno M.; Barkhof, Frederik; Klein, Martin; Moll, Annette C.; Diamant, Michaela; IJzerman, Richard G.; Snoek, Frank J.
ABSTRACT: Objectives: Patients with Type 1 diabetes mellitus (T1DM) are at an increased risk for major depression, but its underlying mechanisms are still poorly understood. In nondiabetic participants, mood disturbances are related to altered subgenual cingulate cortex (SGC) resting-state functional connectivity. We tested for SGC connectivity alterations in T1DM, whether these alterations were related to depressive symptoms, and if depressive symptoms were associated with cognition. Methods: A bilateral SGC seed-based resting-state functional magnetic resonance imaging analysis was performed in 104 T1DM patients and 49 controls without known psychiatric diagnosis or treatment. Depressive symptoms were self-reported using the Center for Epidemiological Studies Depression scale. Cognition was assessed with a battery of standardized tests. Results: In patients versus controls, SGC to right inferior frontal gyrus and frontal pole connectivity was decreased (52 voxels, z valuepeak = 3.56, p cluster-FWE = .002), whereas SGC to bilateral precuneus (33 voxels, z valuepeak = 3.34, p cluster-FWE = .04) and left inferior parietal lobule (50 voxels, z valuepeak = 3.50, p cluster-FWE = .003) connectivity was increased. In all participants, increased depressive symptoms was related to lower SGC to inferior frontal gyrus and frontal pole connectivity ( β = −0.156, p = .053), and poorer general cognitive ability ( β = −0.194, p = .023), information processing speed ( β = −0.222, p = .008), and motor speed ( β = −0.180, p = .035). Conclusions: T1DM patients showed a pattern of SGC connectivity that is characterized by lower executive control and higher default mode network connectivity. Depressive symptoms are partially related to these alterations and seem to exacerbate T1DM-related cognitive dysfunction. Future studies should detail the effect of diagnosed major depressive disorder in this population and establish what alterations are diabetes specific. Abstract : Supplemental digital content is available in the text.